Relationship between intrapreneurship and innovation: a study in participating companies of the IT for APL of Parana southwest (Gestão & Regionalidade, 2017)
This study aimed to verify the existence of relationship between Product Innovation Index (Inip) and intrapreneurial practices in the APL technology companies in the Southwest of Paraná information. Using quantitative methods, with application of two questionnaires to managers and employees responsible for R & D in 47 companies sent in survey format, with the final sample comprised of 16 companies. The analysis was performed using descriptive statistics, followed by calculating the Inip and finally by the r Spearman correlation test. The results revealed that in most companies the product innovation index presented himself down, also showed the perception of the factors that influence the intrapreneurship. However, the correlation between the Inip and intrapreneurship factors did not indicate the existence of relations (significance level of r > 0.005). Only when analyzed separately, intrapreneurship variable pointed moderate positive correlation.